Awake1, an ABC-Type Transporter, Reveals an Essential Role for Suberin in the Control of Seed Dormancy. Issue 1 (14th March 2017) - Fedi, Fabio; O'Neill, Carmel M.; Menard, Guillaume; Trick, Martin; Dechirico, Simone; Corbineau, Françoise; Bailly, Christophe; Eastmond, Peter J.; Penfield, Steven
Abstract : A mutant screen reveals a role for seed coat suberin in temperature-responsive seed dormancy through the exclusion of molecular oxygen from the seed. Abstract: The mother plant plays an important dynamic role in the control of dormancy of her progeny seed in response to environmental signals. In order to further understand the mechanisms by which this dormancy control takes place in Arabidopsis ( Arabidopsis thaliana ), we conducted a forward genetic screen to isolate mutants that fail to enter dormancy in response to variation in temperature during seed set. We show that, for the first of these mutants, designated awake1, the maternal allele is required for entry into strongly dormant states and that awake1 mutants show seed phenotypes shown previously to be associated with the loss of suberin in the seed. We identify awake1 as an allele of ABCG20, an ATP-binding cassette transporter-encoding gene required for the transport of fatty acids during suberin deposition, and show that further suberin-deficient mutants have seed dormancy defects. Seed coat suberin composition is affected by temperature during seed maturation, but this response appears to be independent of ABCG20. We conclude that seed coat suberin is essential for seed dormancy imposition by low temperature and that the exclusion of oxygen and water from the seed by the suberin and tannin layers is important for dormancy imposition.